2008
DOI: 10.1111/j.1365-2591.2008.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of various root canal filling materials ex vivo

Abstract: RealSeal resin filler was nontoxic in this laboratory model. Further investigations are necessary to verify its usefulness in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…In addition, we compared RealSeal core material with gutta-percha because RealSeal core material has similar physical and chemical properties with gutta-percha, and their role and usage in the root canal filling are consistent. As far as we know, gutta-percha is considered to be mildly cytotoxic or even noncytotoxic (11,17). Our results also confirmed that gutta-percha had good biocompatibility.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we compared RealSeal core material with gutta-percha because RealSeal core material has similar physical and chemical properties with gutta-percha, and their role and usage in the root canal filling are consistent. As far as we know, gutta-percha is considered to be mildly cytotoxic or even noncytotoxic (11,17). Our results also confirmed that gutta-percha had good biocompatibility.…”
Section: Discussionsupporting
confidence: 93%
“…After evaluating the cell viability by MTT assay, they found that RealSeal core material had better biocompatibility than gutta-percha (12). Although there were numerous experiments (8,10,14,17) showing an acceptable biocompatibility of RealSeal material, when it was compared with gutta-percha, the result was still controversial (19). The cytotoxicity of RealSeal core material could be due to the biodegradable nature of this material (18).…”
Section: Discussionmentioning
confidence: 92%
“…A substitute for gutta-percha cones, RealSeal System (Sybronendo, Sybron Dental Specialties Inc., Orange, CA, USA), uses Resilon cones and RealSeal Sealer (which is basically Resilon). Previous studies showed lower cytotoxicity levels of Resilon-containing sealers when compared with commonly used sealers 13,15 . The fact that Resilon has low setting time in anaerobic environment 10 may account to a better tissue response.…”
Section: Introductionmentioning
confidence: 88%
“…Gutta-percha is the most common component used in root canal filling materials because it is well tolerated from host tissues [10] but other compounds such as zinc-oxide,eugenol are capable of inducing cytotoxic effects [11-13]. Recently, a new endodontic filling material based on a polyester thermoplastic-filled polymer (Resilon™; Resilon Research LLC, Madison, CT), which looks and performs like gutta-percha, has been developed and put on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [13] showed satisfactory in vitro biocompatibility of both the new self-etching sealer Real Seal 1™ and Real Seal TM  filling materials. The first one showed a mild cytotoxic effect comparable with that of Pulp Canal Sealer (SybronEndo, Orange, CA, USA), a traditional zinc-oxide and eugenol based endodontic sealer currently used in endodontic practice [14].…”
Section: Introductionmentioning
confidence: 99%